Singlet Oxygen Metabolism: From Genesis to Signaling - Dogra, Vivek; Kim, Chanhong (Frontiers in Plant Science, 2020)
Singlet oxygen (1O2) is an excited state of molecular oxygen with an electron spin shift in the molecular orbitals, which is extremely unstable and highly reactive. In plants, 1O2 is primarily generated as a byproduct of photosynthesis in the photosystem II reaction center (PSII RC) and the light-harvesting antenna complex (LHC) in the grana core (GC). This occurs upon the absorption of light energy when the excited chlorophyll molecules in the PSII transfer the excess energy to molecular oxygen, thereby generating 1O2. As a potent oxidant, 1O2 promotes oxidative damage. However, at sub-lethal levels, it initiates chloroplast-to-nucleus retrograde signaling to contribute to plant stress responses, including acclimation and cell death. The thylakoid membranes comprise two spatially separated 1O2 sensors: β-carotene localized in the PSII RC in the GC and the nuclear-encoded chloroplast protein EXECUTER1 (EX1) residing in the non-appressed grana margin (GM). Finding EX1 in the GM suggests the existence of an additional source of 1O2 in the GM and the presence of two distinct 1O2-signaling pathways. In this review, we mainly discuss the genesis and impact of 1O2 in plant physiology.